Crustal Deformation of the Altyn Tagh Fault Based on GPS. Issue 11 (29th November 2018) - Li, Yanchuan; Shan, Xinjian; Qu, Chunyan; Liu, Yunhua; Han, Nana
Abstract: Knowledge of the slip behavior of the Altyn Tagh fault (ATF) has significant implications for our understanding of the tectonic deformation of the Tibetan Plateau. In this study, we process Global Positioning System (GPS) data spanning 2009–2017 across the western ATF, merge the solution with recently published GPS velocities, and obtain a dense GPS velocity field for northern Tibet. We introduce an elastic block model and estimate the fault slip rate, interseismic fault coupling (ISC), and seismic moment accumulation rate along the ATF. The estimated left‐lateral strike‐slip rate of the ATF decreases eastward from 12.8 ± 0.4 mm/a to 0.1 ± 0.2 mm/a. Results show a heterogeneous distribution of ISC along the fault, with the fault locking depth varying from 5 to 20 km. The seismic moment accumulation rate is 2.16–2.37 × 10 18  N m/km along three segments between Sulamu Tagh and Aksay bends, where the accumulated seismic moment over the last five centuries could be balanced by earthquakes with magnitudes of Mw 7.7, Mw 7.6, and Mw 7.8, respectively. We calculate the ratio of the Indo‐Eurasia convergence accommodated by the ATF and find that 10.3% of the convergence is accommodated along the fault by lateral extrusion; quantitative analysis of the strain rate, however, shows that a large part of the northern Tibet is not well described by elastic block rotation. Consequently, we suggest that a hybrid kinematic model that includes both block‐like and continuous deformation is needed to better delineate the crustal deformation of the Tibetan Plateau. Key Points: Altyn Tagh fault slip rate and coupling inverted using new, dense interseismic GPS velocities The three fault segments between Sulamu Tagh and Aksay bends have the potential to rupture in Mw 7.7, Mw 7.6, and Mw 7.8 earthquakes A hybrid kinematic model is needed to delineate the crustal deformation of the Tibetan Plateau